Buying and Selling in Legal, Economic and Social Perspectives - Maya Surya (ISNU Sumatera Utara, 2024)
Buying and selling is a fundamental economic activity in human life and has evolved from a barter system to digital transactions. In law, buying and selling is regulated to ensure justice and protection for transaction actors. From an economic perspective, buying and selling plays a role in economic growth and community welfare, while from a social aspect, buying and selling transactions reflect interactions and trust between individuals. Technological developments have changed buying and selling patterns from conventional transactions to e-commerce, which bring benefits but also pose challenges such as security and consumer protection. This study aims to analyze buying and selling from a legal, economic, and social perspective in order to understand its implications in modern life. The method used is a normative legal approach by examining primary and secondary legal sources, including positive legal regulations, Islamic legal principles, and related literature. The results of the study show that positive law and Islamic law have clear rules in regulating buying and selling transactions in order to create fair trade. Economically, buying and selling encourages market growth, while socially, buying and selling builds harmonious relationships. In conclusion, buying and selling must be carried out with the principles of justice, transparency, and legal protection in order to provide benefits to all parties.